From Therapy Resistance to Targeted Therapies in Prostate Cancer - Moreira-Silva, Filipa; Henrique, Rui; Jerónimo, Carmen (Frontiers in Oncology, 2022)
Prostate cancer (PCa) is the second most common malignancy among men worldwide. Although early-stage disease is curable, advanced stage PCa is mostly incurable and eventually becomes resistant to standard therapeutic options. Different genetic and epigenetic alterations are associated with the development of therapy resistant PCa, with specific players being particularly involved in this process. Therefore, identification and targeting of these molecules with selective inhibitors might result in anti-tumoral effects. Herein, we describe the mechanisms underlying therapy resistance in PCa, focusing on the most relevant molecules, aiming to enlighten the current state of targeted therapies in PCa. We suggest that selective drug targeting, either alone or in combination with standard treatment options, might improve therapeutic sensitivity of resistant PCa. Moreover, an individualized analysis of tumor biology in each PCa patient might improve treatment selection and therapeutic response, enabling better disease management.